The dangers of relentless pursuit: teaching, personal health, and the symbolic/real violence of Teach For America. Issue 6 (2nd November 2018) - Thomas, Matthew A. M.; Lefebvre, Elisabeth E.
ABSTRACT: This paper examines the pressures experienced by teachers as they strive to embody the Teach For America (TFA) motif of 'relentless pursuit'. It draws on interviews conducted with 36 teachers and uses a Bourdieuian analysis to consider the mechanisms of control manifested through socialization and corps member habituation. The findings suggest that corps members experience both symbolic and self-imposed overt violence as they aim to meet the demands of TFA. This has implications for the increasing number of teachers in programs around like TFA as well as the broader discourses of teacher accountability and the teaching profession.